THE RELATION OF EARTHQUAKE FOCI TO FAULTS AND THE MOST RECENT MOVEMENTS OF SOUTHERN ASIA - Khromovskikh V.S. (My University, 1988)
This study presents an analysis of the interrelations between 700 earthquake foci (with M = 6-8 and M > 8) for the period from 1900 to 1980 and fault tectonics and neotectonic deformations in the territory of new folded belts and platforms in Southern Asia rejuvenated in the Cenozoic. The study shows that the seismic activity of ancient faults, that were tectonically passive in the Cenozoic, is nearly the same as that of the Cenozoic counterparts. Besides, it is established that the majority of earthquake foci are related to uplift regions, in which amounts of neotectonic deformation reach intermediate and minimum values, rather than to regions of maximum crustal deformations.
Keywords: Cenozoic; Cenozoic; Кайнозой